Combining hypofractionated radiation therapy with immunotherapy for anorectal malignant melanoma: a case report - Wang, Wei-Jun; Lee, Kuan-Der; Chen, Wei-Yu; Chiou, Jeng-Fong; Lu, Long-Sheng (Therapeutic Radiology and Oncology, 2019)
A 69-year-old man was diagnosed stage II anorectal malignant melanoma. He received radiotherapy which consisted of 25 Gy in 5 fractions to primary lesions and whole pelvis. He started pembrolizumab 3 weeks after the completion of radiotherapy. The treatment was complicated by CTCAE v4.0 grade 3 diarrhea. Ten weeks after radiotherapy, near total regression of the primary lesion as well as lymph nodes were found. The patient continued triweekly pembrolizumab and local recurrence was noted at 9 months after the initial diagnosis. Treating anorectal malignant melanoma with radiation assisted immunotherapy is worth considering and further study is warranted.